Réponses

2014-03-26T23:30:15+01:00
Bonsoir,

calculer : (-5)^-4X(-5)^3 et (-5)^-4/(-5)^3 

(-5)^{-4}\times(-5)^3= (-5)^{-4+3}=(-5)^{-1}=\dfrac{1}{-5}=-\dfrac{1}{5}\\\\\dfrac{(-5)^{-4}}{(-5)^3}= (-5)^{-4-3}= (-5)^{-7}=\dfrac{1}{(-5)^7}=\dfrac{1}{[(-1)\times5]^7}=\dfrac{1}{(-1)^7\times5^7}\\\\=\dfrac{1}{(-1)\times5^7}=\dfrac{1}{-5^7}=-\dfrac{1}{78125}

2014-03-27T00:09:50+01:00

1) (-5)^-4X(-5)^3 =

(-5) ^(-4+3) =

(-5)^-1 =

- 1/5

= - 0.2

2) (-5)^-4/(-5)^3 =

(-5) ^-4 x ( -5) ^-3 =

(-5) ^-7 =

1/(-5)^7=

- 0, 0000128